PENGARUH KOMBINASI PETROGENOL DAN EKSTRAK BELIMBING (Averrhoa carambola L.) TERHADAP PERILAKU MAKAN LALAT BUAH (Bactrocera dorsalis Hend.) - Wati, Rahma; Sumarmin, Ramadhan; Wati, Meliya (STKIP PGRI Sumbar, 2013)
ABSTRACTPetrogenol is attractant that has light Â yellow solution form. Itâs active ingredient is methyl eugenol, a compound of insect pheromones to influence the contra sex for mating, Â Â Â Â Â colonize and eating and beside fruit aroma is able to influence the fruit flies. However the information about the combination of petrogenol and Averrhoa carambola extract on feeding strategy of fruit flies Bactrocera dorsalis is still limited. Based on these problem so have to be made the research about the combination petrogenol influence and Starfruit extract ( Averrhoa carambola L. ) on feeding strategy of fruit flies Bactrocera dorsalis Hend. This research is Â experimental research used Y tube method, with 10 treatment pairs. The research had been done Â from June to August Â in the Laboratory of Zoology Department of Biology, State University of Padang. Feeding strategy observed included searching, grounding and gathering. The observational dates can be analyzed by using Chi - square ( XÂ² ) and compared them with a significance level of 5%. The research result was showed that fastest time of 792.62 seconds on searching is in combination treatment and petrogenol starfruit extract, grounding activities had longest time was 450.85 seconds on petrogenol, and gathering activities had longest time 617.45 seconds on treatment starfruit extracts. XÂ² analysis result for each parameter of Â feeding strategy of fruitflies attitude were found there were significant differences between extracts Averrhoa carambola, extract Averrhoa carambola combination and petrogenolÂ with petrogenol. It can be concluded that the combination of Averrhoa carambola extract and petrogenol is the best attractant for Â feeding strategy of fruit flies activities Bactrocera dorsalis in terms of searching, while the petrogenol is the best attractant in terms of grounding and star fruit extract in terms of gathering is the best attractant.Â